A chromosome-level genome assembly for the Pacific oyster Crassostrea gigas. Issue 3 (25th March 2021) - Peñaloza, Carolina; Gutierrez, Alejandro P; Eöry, Lél; Wang, Shan; Guo, Ximing; Archibald, Alan L; Bean, Tim P; Houston, Ross D
Abstract: Background: The Pacific oyster ( Crassostrea gigas ) is a bivalve mollusc with vital roles in coastal ecosystems and aquaculture globally. While extensive genomic tools are available for C. gigas, highly contiguous reference genomes are required to support both fundamental and applied research. Herein we report the creation and annotation of a chromosome-level assembly for C. gigas . Findings: High-coverage long- and short-read sequence data generated on Pacific Biosciences and Illumina platforms were used to generate an initial assembly, which was then scaffolded into 10 pseudo-chromosomes using both Hi-C sequencing and a high-density linkage map. The assembly has a scaffold N50 of 58.4 Mb and a contig N50 of 1.8 Mb, representing a step advance on the previously published C. gigas assembly. Annotation based on Pacific Biosciences Iso-Seq and Illumina RNA-Seq resulted in identification of ∼30, 000 putative protein-coding genes. Annotation of putative repeat elements highlighted an enrichment of Helitron rolling-circle transposable elements, suggesting their potential role in shaping the evolution of the C. gigas genome. Conclusions: This new chromosome-level assembly will be an enabling resource for genetics and genomics studies to support fundamental insight into bivalve biology, as well as for selective breeding of C. gigas in aquaculture.